Transformasi Perjanjian Kerja Waktu Tertentu (PKWT) di Era Ekonomi Fleksibel: Tantangan Perlindungan Hukum Pekerja Kontrak dan Outsourcing di Jawa Timur - Izzatul Mula; Auliya Ristiani; Abdulrahman Ratuloly; Firza Agung Prakoso (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the transformation of Fixed-Term Employment Agreements (PKWT) in East Java within the context of Indonesia's flexible economy era, particularly following the enactment of the Job Creation Law (UU Cipta Kerja No. 6/2023). The research analyzes the legal protection challenges faced by contract and outsourcing workers in East Java Province from 2020–2025. Using a normative juridical approach combined with empirical data from the Central Statistics Agency (BPS) and the Ministry of Manpower, this study reveals that despite regulatory improvements, significant gaps remain in the implementation of labor protection. Key findings indicate that contract workers in East Java, estimated at 59.17% of the informal workforce in 2024, face uncertainties regarding contract duration, compensation rights, and social security. The study recommends strengthening supervision mechanisms, clarifying regulations on gig economy workers, and enhancing bipartite negotiation processes to ensure balanced protection between business flexibility and workers' fundamental rights, while also promoting legal certainty and sustainable employment relations in the regional labor market.